Klasifikasi Sentimen Masyarakat di Media Sosial Twitter terhadap Calon Presiden 2024 Prabowo Subianto dengan Metode K-NN - Avaldy Rahmat Rivita; Yusra; Muhammad Fikry (STMIK Budi Darma, 2023)
The 2024 Republic of Indonesia Presidential Election is a democratic stage to determine the President of the Republic of Indonesia and Vice President of the State of Indonesia for the 2024-2029 period which is scheduled to take place on Wednesday, 14 February 2024. This election is the fifth direct presidential and vice presidential election in Indonesia. Several parties have currently nominated or selected their presidential candidates for the 2024 presidential election. Three presidential candidates have emerged, namely Prabowo Subianto, Ganjar Pranowo, and Anies Baswedan. Based on a survey, Prabowo Subianto is the presidential candidate (capres) with the highest electability compared to other competitors. The society's view of the 2024 presidential candidate, especially Prabowo Subianto, has raised many pros and cons. Society's view can be seen on social media, like one of this is the Twitter. This study aims to classify public sentiment towards the Presidential Candidate (capres) Prabowo Subianto on Twitter. The amount of data used is 2100 tweets which are collected based on the keywords